Concordance of common data elements for assessment of subjective cognitive complaints after mild-traumatic brain injury: a TRACK-TBI Pilot Study. (29th July 2018) - Ngwenya, Laura B.; Gardner, Raquel C.; Yue, John K.; Burke, John F.; Ferguson, Adam R.; Huang, Michael C.; Winkler, Ethan A.; Pirracchio, Romain; Satris, Gabriela G.; Yuh, Esther L.; Mukherjee, Pratik; Valadka, Alex B.; et al.
ABSTRACT: Objective : To determine characteristics and concordance of subjective cognitive complaints (SCCs) 6 months following mild-traumatic brain injury (mTBI) as assessed by two different TBI common data elements (CDEs). Research design : The Transforming Research and Clinical Knowledge in Traumatic Brain Injury (TRACK-TBI) Pilot Study was a prospective observational study that utilized the NIH TBI CDEs, Version 1.0. We examined variables associated with SCC, performance on objective cognitive tests (Wechsler Adult Intelligence Scale, California Verbal Learning Test, and Trail Making Tests A and B), and agreement on self-report of SCCs as assessed by the acute concussion evaluation (ACE) versus the Rivermead Post Concussion Symptoms Questionnaire (RPQ). Results : In total, 68% of 227 participants endorsed SCCs at 6 months. Factors associated with SCC included less education, psychiatric history, and being assaulted. Compared to participants without SCC, those with SCC defined by RPQ performed significantly worse on all cognitive tests. There was moderate agreement between the two measures of SCCs (kappa = 0.567 to 0.680). Conclusion : We show that the symptom questionnaires ACE and RPQ show good, but not excellent, agreement for SCCs in an mTBI study population. Our results support the retention of RPQ as a basic CDE for mTBI research. Abbreviations : BSI-18: Brief Symptom Inventory; 18CDEs: common data elements; CT: computed tomography; CVLT: California Verbal Learning Test; ED: emergency department; GCS: Glasgow coma scale; LOC: loss of consciousnessm; TBI: mild-traumatic brain injury; PTA: post-traumatic amnesia; SCC: subjective cognitive complaints; TBI: traumatic brain injury; TRACK-TBI: Transforming Research and Clinical Knowledge in Traumatic Brain Injury; TMT: Trail Making Test; WAIS-PSI: Wechsler Adult Intelligence Scale, Fourth Edition, Processing Speed Index